Relationship Knowledge and PHBS Attitudes to Personal Hygiene at SMP Negeri 1 Kuala Kabupaten Langkat 2020 - Sapnita, Sapnita (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
Clean and healthy living behavior (PHBS) in schools is a set of behaviors practiced by students, teachers and the school community on the basis of awareness as a result of learning, so that they can independently prevent disease, improve their health, and play an active role in creating a healthy environment. The purpose of this study was to determine the knowledge and attitudes of clean and healthy living behavior (PHBS) on personal hygiene in students of SMP Negeri 1 Kuala KabupatenLangkat in 2020. The method used in this study uses a quantitative method with a Cross Sectional approach. This study used a proportional random sampling technique in children aged 12-16 years or grades VIII and IX as many as 63 respondents. The instruments used are questionnaires and observation of knowledge and attitudes. Data analysis used Chi Square test at < 0.05.The results of the analysis show that there is no significant relationship between the independent variable, namely personal hygiene (personal hygiene) with the dependent variable, namely clean and healthy living behavior (PHBS), which has a p value = 0.320. This researcher is expected to be a reference for further research to know the dominant factors.